Temporal Stability Analysis of Resin Yield of Natural Regenerated Chir Pine (Pinus roxburghii Sargent) in Himachal Pradesh - Bharti; Gupta, R. K.; Mahajan, P. K.; Sharma, K. R. (Indian Forester, 2016)
The present investigation entitled ’Temporal Stability analysis of resin yield of natural regenerated Chir pine (Pinus roxburghii Sargent) in Himachal Pradesh.’ was carried out during the year 2012-13 with the aim to identify the stable diameter classes with respect to resin yield obtained from Pinus roxburghii. Secondary data on resin yield for 145 trees for seven years w.e.f. year 2005 to year 2011 were taken from the Department of Forest Products, Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh. The tree set of 145 trees remain same for all the years. These trees were divided into seven diameter classes i.e. 30-35 cm, 35-40 cm, 40-45 cm, 45-50 cm, 50-55 cm, 55-60 cm and 60-65 cm depending upon the variability among data. Two stability models viz. Finlay and Wilkinson’s model (1963) and Eberhart and Russell’s model (1966) were used to identify the stable diameter class for the production of resin. Pooled analysis of variance was performed to detect the presence of diameter class (D) Ã— year (Y) interaction. The effects due to Y, D and D Ã— Y interaction were found to be significant. Finlay and Wilkinson’s model suggested that the diameter class 40-45 cm had the mean (D) greater than the overall mean and regression coefficient bi was nearly equal to one. Eberhart and Russel’s model indicated that the diameter class 40-45 cm had (0.35) which 2 was greater than zero, regression coefficient bi (0.872) which was nearly equal to one and low (s d). Thus, diameter i class 40-45 cm was identified as stable diameter class with respect to resin yield obtained from Pinus roxburghii. Therefore, it may be concluded that diameter class 40-45 cm was most stable for resin yield.